Factors influencing migration among Nepalese nurses - Baral, R; Sapkota, S (Journal of Chitwan Medical College, 2015)
Migration of Health workers has devastating consequences leading to loss of health workers in the nation of origin. This research was carried out to identify the push factors related to migration of Nurses from Nepal to other developed countries. A cross sectional descriptive study was conducted via different social medias. The data was collected from 67 migrated Nepalese Nurses to: Australia, USA, UK and Canada. Self-administered questionnaire in the form of “Google docs form” was used to collect data from respondents. The study showed that 70.15% of respondents were of 20-29 years of age. In the study, 38.80% of respondents were from Australia followed by 31.34% from USA, 16.43% from UK and 13.43% from Canada. When the researcher advised respondents to prioritize the major cause of migration by giving 1 to major and 8 to least responsible factor of migration, the study revealed that personal ambition (Mean: 3.18), lack of job and career opportunities in Nepal (Mean: 3.57), economical factors (Mean: 3.2), and job dissatisfaction (Mean: 4.90) are the main causes of migration among Nepalese Nurses. This study also showed that 55.22% of respondents were not satisfied with their job in Nepal. 53.74% and 43.28% of the respondents are satisfied and highly satisfied respectively with their job in abroad. It can also be concluded that lack of modern facilities merely is not only the motivating factor for migration among Nepalese nurses, age and personal ambition also play a role in migration.